Strategi Komunikasi BKKBN (Badan Koordinasi Keluarga Berencana Nasional) Melalui Program Keluarga Berencana - Holiseh Holiseh; Evi Satispi; Diaz Tarakarti Gusman; Shafira Azahra; Risya Amalia (Jurnal Akuntan Publik, 2023)
This journal discusses the Government's Communication Strategy through the Family Planning Program. This study aims to provide knowledge about communication strategies for family planning programs to the community. The research method used is a qualitative approach with a descriptive method. The data sources in this study were obtained from references such as journals, books, and other written sources. The results of the family planning program is an activity held by the BKKBN which is a communication medium to become a medium for disseminating the family planning program. This family planning program needs to be well communicated and socialized, so that the younger generation of Indonesia in particular really gain knowledge and have attitudes in accordance with what is desired by the BKKBN. Therefore, a good communication strategy is needed so that the message to be conveyed to the younger generation can be received and realized properly. conclusions regarding the communication strategy of the BKKBN in the Family Planning program to the community to form community awareness itself through a communication strategy.